Case Report: Acute Pancreatitis with Necrosis Leading to Chronic Pancreatitis and Complications - G, Radhika.; .S, Vignesh; Dheenadhayalan, M.; Karthickeyan, K.; Shanmugasundaram, P.; Sundar Sri, M. K. (Journal of Neonatal Surgery, 2025)
Acute pancreatitis (AP) is a common clinical entity and one of the leading causes of morbidity and mortality from local and systemic complications. Recent insights into diagnosis and management, as well as common interventions for AP, pseudocysts, and pancreatic duct involvement, have been discussed in this article. Emerging literature from endoscopic and radiological evidence-based imaging and potential biomarkers has modified its management approach. Artificial intelligence, machine learning-based precision medicine and application of antioxidants like quercetin may have potential therapeutic implications. Further, advanced cross-sectional imaging including CECT and MRI is useful for early detection and management in necrotizing pancreatitis or pseudocyst formation. In addition, organ failure, infection, and systemic involvement like sarcopenia should also be noted for overall impact and prognosis. The impact of individualized treatment as per the needs using both conventional and novel methods is beneficial for better care. Endoscopic retrograde cholangiopancreatography (ERCP) and parenteral nutrition in the setting of critical illness have also been added to the algorithm for overall improvement.